Numerical Simulation and Experimental Studies on Stationary Shoulder Friction Stir Welding of Aluminum Alloy T-Joint - Wang, Chungui; Deng, Jun; Dong, Chunlin; Zhao, Yunqiang (Frontiers in Materials, 2022)
The application of the corner stationary shoulder friction stir welding (CSSFSW) on T-shaped structures is exceptional, and adequate research is still required for the related theory. In this paper, taking 5083 aluminum alloy as the workpiece, based on the Arbitrary Lagrangian Eulerian (ALE) method, a three-dimensional thermomechanical coupled model of the CSSFSW process was established. The temperature field and material flow were simulated and analyzed during the welding process. The friction heat formed an elliptical temperature gradient range, and expanded with the progress of the welding. The highest temperature of up to 575 ℃ was recorded on the advanced side, which is higher than that on the retreating side (about 532 ℃). The forward and backward material flow directions were found to be opposite to each other. In the traverse direction, the material on both sides flowed upward along the pin and downward under the action of the stationary shoulder at the top. The difference between the simulated and the measured temperature lies within 7%, and the material flow also has good agreement with the experimental results.